Diseños geométricos en los mosaicos del Conventus Astigitanus - Vargas Vázquez, Sebastián, (Archaeopress Roman archaeology ;, 2016)
This volume focuses on the study of the geometric designs documented in the mosaics of the Conventus Astigitanus, one of the four conventi iuridici of Roman Baetica.